Spatiotemporal Variation in Ecological Risk on Water Yield Service via Land-Use and Climate Change Simulations: A Case Study of the Ziwuling Mountainous Region, China - Jin, Tiantian; Yan, Lingling; Wang, Shimei; Gong, Jie (Frontiers in Environmental Science, 2022)
Scientists have paid attention to assessing the change of ecosystem service risk under human activities, yet few works have focused on the water yield risk induced by land-use and climate change. In this study, a framework combining water yield with ecological risk for service enhancement and human adaptation was established. The framework was applied to explore the spatiotemporal variation of water yield service and its ecological risk via land-use and climate change scenarios in the Ziwuling Mountainous Region (ZMR), China, using the InVEST, CA-Markov, and TOPSIS model. The water yield service decreased from 69.19 mm in 1990 to 47.72 mm in 2017 in the ZMR. The water yield service in the southeast ZMR was larger than that in the northwest. The water yield service risk was high and increased first then decreased from 1990 to 2017 in the ZMR. The high and higher risk subareas were distributed in the middle and north of the ZMR. The water yield service is the highest under the EC126 scenario (48.09 mm in 2050, 43.73 mm in 2100) and the lowest under the EP585 scenario (43.52 mm in 2050, 40.62 mm in 2100). The water yield service risk of the EP558 scenario is the largest one, with an area ratio of the high risk of 83.95% in 2050 and 85.33% in 2100. We suggest developing water-saving agriculture and high-efficiency industrial systems, as well as ecological restoration and integrated forest social-ecological management for risk alleviation, service enhancement, and sustainable development.